Association between preoperative hemoglobin and postoperative moderate and severe anemia among patients undergoing primary total knee arthroplasty: a single-center retrospective study - Guorui Cao; Xiuli Yang; Hong Xu; Chen Yue; Zeyu Huang; Shaoyun Zhang; Songtao Quan; Junna Yao; Minglu Yang; Fuxing Pei (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background Postoperative moderate and severe anemia (PMSA) has been a serious perioperative complication in primary total knee arthroplasty (TKA). However, the ideal cutoff values to predict PMSA is still undetermined. The aim of this study was (1) to identify the risk factors associated with PMSA and (2) to establish the cutoff values of preoperative hemoglobin (HB) associated with increased PMSA in primary TKA. Methods We identified 474 patients undergoing primary TKA and separated those in which PMSA (HB was less than 110 g/L on postoperative day 1 and 3) was developed from those without PMSA. Multivariate logistic regression model was used to identify independent risk factors for PMSA. Area under the receiver-operator curve (AUC) was used to determine the best-supported preoperative HB cutoff across all the patients. Results The PMSA rate in primary TKA was 53.2%. Significant risk factors were lower preoperative HB (OR [odds ratio] = 1.138, 95% CI [confidence interval] = 1.107–1.170, p < 0.001) and more intraoperative blood loss (OR = 1.022, 95% CI 1.484–4.598, p < 0.001). A preoperative HB cutoff value that maximized the AUC was 138.5 g/L for men (sensitivity: 79.4%, specificity: 75.0%) and 131.5 g/L for women (sensitivity: 74.7%, specificity: 80.5%), respectively. Conclusion We should recognize and consider the related risk factors to establish specific, personalized risk assessment for PMSA, including preoperative HB and intraoperative blood loss. Of these, preoperative HB was a referable tool to predict PMSA in primary TKA.